ULTRAMAN GAIA : ONCE AGAIN GAIA - Jissoji Akio; Tsuburaya Eiji (BCI Eclipse Co. LLC, 2006)
The Science Patrol defends the Earth from monsters and alien invaders with the help of the red and silver superhero from Nebula M78, Ultraman